Is Testicular Torsion a Real Problem in Pediatric Patients With Cryptorchidism? - Komarowska, Marta Diana; Pawelczyk, Alicja; Matuszczak, Ewa; Dębek, Wojciech; Hermanowicz, Adam (Frontiers in Pediatrics, 2021)
Purpose: To present management and outcomes of patients with cryptorchidism suffering from testicular torsion. Methods: This is a retrospective review of pediatric patients with torsion of undescended testes, who were treated between 2009 and 2019. We recorded: the age, symptoms, duration of torsion, results of physical examination, surgery findings, and additional treatment. Additionally, an extensive online literature search was performed to identify other similar cases. Results: We identified 9 boys with torsion of the undescended gonad, which represented 4.7% of all 192 boys with testicular torsion. The mean age of boys with torsion of undescended testis was 8.7 years. The mean duration of symptoms in our study group was long and it was up to 28.5 hours. All patients had inguinal canal exploration. In 8 cases, testicular necrosis and primary orchidectomy was performed. Furthermore, 52 cases were identified in the literature and reviewed. Conclusion: According to clinical experience and available studies, torsion of male undescended gonads is a comparatively rare condition. Nevertheless, diagnosis is still delayed and connected with inevitable orchidectomy. Summary: Authors present 9 cases of boys with torsion of undescended testes. They represented 4.7% of all boys with testicular torsion treated during 10 years in Pediatric Surgery Department. The mean age of boys with torsion of undescended testis was 8.7 years. The mean duration of symptoms was long and it was up to 28.5 hours. All patients were operated on, in 8 cases necrotic testicle was removed. Torsion of undescended testicle is quite rare, in most cases diagnosis is delayed and because of that, boys are subjected to removal of the testicle.